PENGARUH LATIHAN SMALL SIDED GAMES TERHADAP AKURASI PASSING PADA EKSTRAKURIKULER FUTSAL SMAN 3 PALOPO - Mayang Ribka; Suaib Nur; Rachmat Hidayat; Irsan Kahar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of Small-Sided Games training on passing accuracy in the futsal extracurricular program at SMAN 3 Palopo. This research employed an experimental method with a one-group pretest-posttest design. The study was conducted at SMAN 3 Palopo, located in Palopo City, South Sulawesi. The population consisted of all students participating in the futsal extracurricular program, totaling 25 students, all of whom were selected as the sample using a saturated sampling technique. Data analysis involved describing and interpreting the collected data from the pretest and posttest results to evaluate improvements in passing accuracy after the Small-Sided Games training. Statistical procedures included normality tests, homogeneity tests, and t-tests, analyzed using SPSS version 22. The training was carried out over 16 sessions during July–August. The descriptive findings showed that the average pretest score was 2.76, while the average posttest score increased to 7.56. Furthermore, the paired sample t-test (2tailed) revealed that the calculated t-value (33.941) was greater than the critical ttable value (2.059) at α = 0.05, thus rejecting H0 and accepting Ha. These results indicate that Small-Sided Games training has a significant effect on passing accuracy in the futsal extracurricular program at SMAN 3 Palopo.